Reading Wallace Stevens in Plato’s Light - Penas Ibáñez, Beatriz (Miscelánea: A Journal of English and American Studies, 1992)
Even though Plato and Aristotle hold different standpoints on the matter of mimesis, both authors have laid the foundation stone for a never ending discussion on the problem of representation which this paper will retake and respectfully use for the sake of illuminating Wallace Stevens’s texts. It is my assumption in this article that Stevens shares with Plato a certain view of the worlds of fact and fiction which is not to be severed from the related concept of mimesis which sustains it. In this they both diverge from the paths of realism as opened by Aristotle’s philosophical writings.